2007
DOI: 10.1111/j.1365-3156.2007.01825.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment‐seeking behaviour, cost burdens and coping strategies among rural and urban households in Coastal Kenya: an equity analysis

Abstract: SummaryIll-health can inflict costs on households directly through spending on treatment and indirectly through impacting on labour productivity. The financial burden can be high and, for poor households, contributes significantly to declining welfare. We investigated socio-economic inequities in self-reported illnesses, treatment-seeking behaviour, cost burdens and coping strategies in a rural and urban setting along the Kenyan coast. We conducted a survey of 294 rural and 576 urban households, 9 FGDs and 9 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
200
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(213 citation statements)
references
References 48 publications
12
200
1
Order By: Relevance
“…Consistent with this study, Chuma et al (2007) introduced place of living among factors effective on treatment-seeking behavior, with this difference that 20.1% of people in rural regions and 9.3% of people in urban regions who reported suffering from acute illness during the 2 weeks before study, did not seek any treatment and about chronic illness a similar pattern was observed (56.9 villagers, 44.9 citizens).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with this study, Chuma et al (2007) introduced place of living among factors effective on treatment-seeking behavior, with this difference that 20.1% of people in rural regions and 9.3% of people in urban regions who reported suffering from acute illness during the 2 weeks before study, did not seek any treatment and about chronic illness a similar pattern was observed (56.9 villagers, 44.9 citizens).…”
Section: Discussionsupporting
confidence: 67%
“…Designation of sufficient resources for health section could improve mortality statistics [9]. Awareness of treatment-seeking behavior could include total rate of benefiting from health-care services and also special information in this ground that who use what kind of health-care services and this service is provided from which source [10]. Generally, 69% of total cost of health section is highly influenced by consumption behavior [11].…”
Section: Introductionmentioning
confidence: 99%
“…This emphasizes the earlier point that it is also important to explore the extent to which households do not use services because of inability to pay. It was reported that availability of services proved to be positively correlated with catastrophic spending in low and middle income countries but not in high income countries [27,28]. In many other European countries health insurance coverage is very comprehensive and OOP payments are either absent or do not differ across provider alternatives [29].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed, individual-level socioeconomic data are required to examine possible interactions between travel time and socioeconomic factors that influence care-seeking behaviour, including the effect of wealth on mode of transport choice. 32,33 Such data are not currently available for our study area, justifying our use of sublocation-level maternal education variables as the best available proxy: this is an important limitation in a setting where household finances are likely to be a key determinant of access to hospital care. We do not expect any confounding by immunization status given the high levels and limited geographic variations in vaccination coverage in Kilifi.…”
Section: Discussionmentioning
confidence: 99%